Emotion Processing and the Role of Compassion in Psychotherapy from the Perspective of Multiple Selves and the Compassionate Self - Kenichi Asano (Case Reports in Psychiatry)
Emotion processing is an important factor for successful psychotherapy. Clients tend to suffer from maladaptive emotions, which contribute to states of confusion, rumination, and stagnation. The therapist should demonstrate adequate empathy and understanding of the client’s complaints to help the client to recognize and respect their own emotions and desires. In most cases, there is more than one desire, and each desire should be confronted. The compassionate self exercises are helpful to distinguish and integrate confused states. In this report, the author introduces a case in which the therapist helped a client to process emotional experiences by leading the client to pay attention to her own emotional responses. The client accessed multiple desires for each emotion and recognized the context for each. To integrate multiple desires and contexts, the therapist used multiple selves exercises from Compassion Focused Therapy. The compassionate self exercises play a role in integrating complicated emotions and in directing the client toward making an adequate choice independently. On its own, processing emotional experiences can induce adaptive and healthy desires; however, using compassionate self exercises helps the client to integrate complicated emotions and to approach their own values in a more direct way.